Brazilian network of human milk banks: a network based on trust - Mariana Simoes Barros; João Aprigio Guerra de Almeida; Alejandro Guillermo Rabuffetti (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2018)
This article bases on a study that aimed to identify the existing links in the rBLH-BR - Rede Brasileira de Bancos de Leite Humano (Brazilian Network of Human Milk Banks). It is an exploratory-descriptive research of qualitative nature where interviews were carried out with all coordinators of state reference centers to human milk banks and with members of the CNBLH - Comissão Nacional de Bancos de Leite Humano (National Commission to Human Milk Banks). The results demonstrate that the sense of belonging, mutual aid, freedom to express themselves and harmony reflect the trust placed in the rBLH-BR. It was verified the presence of association bonds between all actors in the rBLH-BR.